Analysis of Phenolic Compounds in Taraxaeum mongolicum Hand Mazz by a-Cyclodextrin Modified Capillary Zone Electrophoresis After Microwave-Assisted Extraction - LU, YUANQI; LI, HUIXIN (Asian Journal of Chemistry, 2010)
An a-cyclodextrin (a-CD) modified capillary zone electrophoretic (CZE) method has been developed to determine 4 kinds of phenolic compounds (chlrorogenic acid, isoquercitrin, quercetin and caffeic acid) in Taraxaeum mongolicum Hand Mazz. The effects of buffer pH and concentration, applied voltage and a-CD concentration on separation were investigated. The optimum electrophoretic conditions are as follows: 50 mmol L-1 boric acid-50 mmol L-1 borax (pH 9.0)-4 mmol L-1 a-cyclodextrin as the running buffer, applied voltage of 25 kV and capillary temperature of 25 ºC. Under the optimized conditions, a good linearity between the peak area and the concentration was found in the range of 3-200, 3-200, 1-100 and 1-200 μg mL-1 for chlorogenic acid, isoquercitrin, quercetin and caffeic acid, respetively. The relative standard deviation in migration time and peak area was 0.19 and 1.79 % for chlorogenic acid, 0.34 and 2.58 % for isoquercerin, 0.20 and 2.78 % for quercetin, 0.23 and 2.65 % for caffeic acid. The detection limits of the 4 phenolic compounds ranged from 0.20 to 0.56 μg mL-1. The recoveries of the 4 phenolic compounds ranged between 92.6 and 106.0 %.